2021
DOI: 10.1186/s40942-021-00335-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety of various parameter sets with navigated microsecond pulsing laser in central serous chorioretinopathy

Abstract: Background Subthreshold microsecond pulsing laser is an increasingly common treatment approach for central serous chorioretinopathy. However, there is no literature available on the safety of microsecond laser using different fluence settings in this disease. While many publications can be obtained from conventional microsecond pulsing lasers, few parameter sets are published with the navigated microsecond pulsing laser. Therefore, this study aims to investigate the safety of different paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Considering that PDT is an invasive procedure that can rarely carry risks of collateral retinal damage, several authors suggest YSML as a competitive alternative for chronic CSC [ 75 , 97 ]. Moreover, in the last 2 years there has been a verteporfin shortage worldwide that still represents a problem in many countries [ 98 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Considering that PDT is an invasive procedure that can rarely carry risks of collateral retinal damage, several authors suggest YSML as a competitive alternative for chronic CSC [ 75 , 97 ]. Moreover, in the last 2 years there has been a verteporfin shortage worldwide that still represents a problem in many countries [ 98 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…SML safety profile in CSC patients has been evaluated by observing only morphological parameters such as RPE and outer retinal layer atrophy [ 21 , 25 ]. Chhablani et al reported improvement in SRF reduction with no retinal tissue damage on optical coherence tomography (OCT) when using eight different micropulse laser parameters in CSC patients in a real-world setting [ 26 ]. Studies in retinal conditions showed decreased retinal sensitivity [ 27 ] and mfERG responses [ 28 ] in areas without morphological changes on multimodal imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the Navilas® laser system uses a digital imaging concept that allows a computer-assisted application of the laser, thus limiting the risk of overlapping spots. 10 …”
Section: Discussionmentioning
confidence: 99%